Entomological surveillance for malaria control at a gold mine in Sadiola District, western Mali - Wragge, Sue-Ellen (My University, 2021)
The aim of this research was to determine if vector control methods used in the SEMOS gold mine vector control programme (Kayes district, south-western Mali), were effective in reducing malaria transmission. Historical entomological surveys to manage insecticide resistance in the main Anopheles mosquito vectors were compared with current surveys. Mosquitoes were collected from potential breeding habitats within and adjacent to the control zone. Adult Anopheles mosquitoes were exposed to insecticides using standard insecticide susceptibility bioassays and subsequently identified using morphological keys and molecular methods for members of the Anopheles gambiae complex and An. funestus group. The Walter Reed Biosystematics Unit’s West African adult keys were used for identifying Culex and Aedes mosquitoes. Insecticide resistance data and species identification from 2018 were compared with previous surveys in 2006, 2011, 2014 and 2016. In all years, An. gambiae and An. arabiensis were present and most abundant. Anopheles coluzzii was present in all five years in small numbers. Anopheles funestus was collected in four of the five years, An. leesoni in 2016, An. rivulorum in 2006 and An. rivulorum-like in 2018. The last species is recorded for the first time in Mali. Rotation of insecticide classes using a mosaic indoor spray pattern, has resulted in maintaining An. arabiensis susceptibility to five of the insecticides in three classes tested in 2018, with only resistance to DDT (86.9% mortality) still present. Including the treatment of pit toilets into the SEMOS vector control programme has reduced nuisance and other vector mosquito species in the area.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2021